P079 Attenuation of inflammation and histologic production-dependent improvement by engineered high acetate producing Saccharomyces boulardii in DSS-induced colitis. (30th January 2023) - Deleu, S; Trindade de Carvalho, B; Jacobs, I; Arnauts, K; Deprez, L; Vissers, E; Lenfant, M; De Hertogh, G; Huys, G; Thevelein, J; Raes, J; Vermeire, S; et al.
Abstract: Background: It has been hypothesized that the probiotic potential of the yeast Saccharomyces boulardii ( Sb ) is associated with its acetate production. This SCFA is of interest in IBD due to its cross-feeding potential with beneficial butyrate-producing bacteria and low toxicity to epithelial cells . Our previous in vitro work supports this hypothesis (Deleu et al, 2022) but still requires in vivo validation. Therefore, we evaluated the effect of different engineered Sb strains producing variable amounts of acetate in DSS-induced colitis in mice. Methods: Nine week old female C57/Bl6 mice (N=120) were allocated to 12 treatment groups receiving drinking water or 2.75% DSS in combination with PBS (control), Baker's yeast (non-probiotic control), SDH1 (non-acetate producing Sb ), ENT (transient acetate producing Enterol strain-probiotic control), SbP (high acetate producing Sb ) and ENT3 (extra high acetate producing Sb ). Disease activity including weight loss, diarrhoea and the presence of occult blood was scored daily. On day 7, the DSS groups were transferred to regular drinking water and on day 14 mice were sacrificed. Colonic tissue and blood were collected for resp. histologic and cytokine analysis. Results: Disease activity, determined by the area under the curve, in DSS subgroups was lower for SbP compared to PBS and Baker's yeast (both p <0.05). Remarkably, Sb SDH1 showed even higher disease activity compared to the Sb strains ENT, SbP and ENT3 (all p <0.05). At sacrifice, macroscopic damage score in DSS subgroups was lower for SbP and ENT3 (both p <0.05) compared to Sb SDH1 and the colon weight/length-ratio was decreased for ENT and SbP compared to Sb SDH1 (resp. p =0.06 and p =0.08). Higher histologic inflammation was noted in the non- or only transient-acetate producing strains on DSS compared to healthy PBS control (all p <0.05), whereas this increase was not observed for both high-acetate producing strains SbP and ENT3 on DSS ( p=NS ). Lower IL1β, IL2 and IL4 concentrations for DSS groups on SbP and ENT3 compared to DSS groups on Sb SDH1 and ENT were observed (all p<0.05). In contrast, IL10, TNFα and KC/GRO were lower for the DSS groups on Sb SDH1 and ENT compared to DSS groups on SbP, ENT3, and even PBS for IL2 and 4 (all p<0.05). Conclusion: Engineered high acetate producing Sb strains show a significant trend towards improved attenuation of DSS-induced colitis compared to the parent Sb strain on disease activity, macroscopic damage score and show production-dependent response on histology. Mixed pro-inflammatory serum profiles were observed potentially pointing in the direction of other effects of acetate accumulation. Together with our previous in vitro work, these data indicate a role for Sb -produced acetate in attenuating inflammation.